Perbandingan Benefit Cost Analysis Laboratorium Dengan Metode KSO Reagen Rental dan Cost per Reportable Result - Shinta Dewi, Viola; Astiena, Adila Kasni; Semiarty, Rima; Yurniwati, Yurniwati; Yulia, Dwi; Putra, Abdi Setia (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Healthcare financing is the foundation of sustainable hospital services, including laboratory units that have high needs for equipment, reagents, and maintenance. Inefficient financing can hinder service quality and reduce the hospital's capacity to meet patient needs. Dr. M. Djamil Padang General Hospital, as a national referral hospital, faces these challenges, particularly in hematology testing, which dominates the laboratory service load. Although the number of tests decreased in 2024, laboratory costs actually increased beyond the budget ceiling, forcing a change in the financing method from CPRR back to Reagent Rental Operational Cooperation. This condition emphasizes the need for a comprehensive evaluation of the laboratory financing scheme through Benefit Cost Analysis to determine the most efficient and sustainable method. Methods: This study used a mixed method approach with a sequential explanatory strategy to analyze the financing of hematology laboratory tests. Quantitative research was conducted through benefit and cost analysis. The qualitative approach was conducted through in-depth interviews with informants from various hospital units. Results: The monetary benefit of the reagent rental KSO was Rp12.903.315.976 and the CPRR was Rp12.229.845.066. The total cost of the reagent rental KSO was Rpp2.485.694.024,- and the CPRR was Rp3.159.164.934. The Benefit Cost Ratio for the KSO reagent rental is 4.44, while that for the CPRR is 3.84. The selection of a laboratory operational cooperation model is not only a matter of cost efficiency but also considers the clinical context, internal capacity, and long-term strategy of the hospital. All informants felt that both the reagent rental KSO and the CPRR KSO had their own advantages and disadvantages, and in choosing a KSO, they looked more at its use and the hospital's current financial condition. Conclusion: Both KSO models are feasible because they generate positive NPV and BCR > 1. Financially, KSO Reagen Rental is more profitable than KSO CPRR